Large-Scale Group Decision-Making Model with Cooperative Behavior Based on Social Network Analysis considering Propagation of Decision-Makers' Preference. (9th July 2022) - Bai, Shizhen; He, Hao; Ge, Mengke; Yang, Ruobing; Luo, Dan; Bi, Xinrui
Abstract : This paper proposes a large-scale group decision-making model with cooperative behavior based on social network analysis considering propagation of decision-makers' preference, which is applicable for large-scale group decision-making problems in social network contexts. The main contributions of our research are three aspects. Firstly, a novel calculation method of cooperative degree, hesitant degree, and noncooperative degree is developed, which considers both the network status and the preference for each DM, and thereby it can better represent the current state for each DM. Then, the determination method of each DM's weight is presented, which considers both the individual network centrality and preference similarity degree. In addition, the score for the current cooperation situation is performed, and the improvement algorithm of the increase of cooperative degree and the decrease of noncooperative degree is designed to enhance the quality of the decision-making results. Finally, the proposed model has demonstrated the validity and superiority based on the comparative and sensitive analysis through a practical example.